SNP array genomic analysis of matched pairs of brain and liver metastases in primary colorectal cancer - Brandt, Vivian-Pascal; Holland, Heidrun; Wallenborn, Marco; Koschny, Ronald; Frydrychowicz, Clara; Richter, Mandy; Holland, Lydia; Nestler, Ulf; Sander, Caroline (Journal of cancer research and clinical oncology, 2023)
Brain metastasis formation is a rare and late event in colorectal cancer (CRC) patients and associated with poor survival. In contrast to other metastatic sites, the knowledge on chromosomal aberrations in brain metastases is very limited.